Viscoelastic and Functional Properties of Cod-Bone Gelatin in the Presence of Xylitol and Stevioside - Nian, Linyu; Cao, Ailing; Wang, Jing; Tian, Hongyu; Liu, Yongguo; Gong, Lingxiao; Cai, Luyun; Wang, Yanbo (Frontiers in Chemistry, 2018)
The physical, rheological, structural and functional properties of cod bone gelatin (CBG) with various concentrations (0, 2, 4, 6, 10 and 15%) of low-calorie sweeteners (xylitol (X) and stevioside (S)) to form gels were investigated. The gel strength of CBGX increased with increased xylitol due presumably to hydrogen bonds between xylitol and gelatin, but with CBGS the highest gel strength occurred when S concentration was 4%. Viscosity of CBGS samples were higher than CBGX due to S’s high molecular mass. The viscoelasticity (G′ and G″), foaming capacity and fat binding capacity of CBGX were higher while foam stability was lower. The emulsion activity and emulsion stability of CBGX were a little lower than CBGS at the same concentration. The structure of X is linear making it easier to form a dense three-dimensional network structure, while the complex cyclic structure of S had more difficulty forming a network structure with cod bone gelatin. Therefore, X may be a better choice for sweetening gelatin gels.